Evaluation Design for The Two Georgias Initiative: Assessing Progress Toward Health Equity in the Rural South. (April 2023) - Kegler, Michelle C.; Hermstad, April; Haardörfer, Regine; Arriola, Kimberly Jacob; Gauthreaux, Nicole; Tucker, Samantha; Nelson, Gary
As persistent inequities in health gained increased attention nationally due to COVID-19 and racial justice protests in 2020, it has become increasingly important to evaluate both the process and outcomes associated with coalition-based efforts to address health inequities. The Two Georgias Initiative supports coalitions in 11 rural counties to (1) achieve greater health equity, (2) improve health and health care, (3) build healthier rural communities and improve social conditions that impact the health of rural populations, and (4) build community, organizational, and individual leadership capacity for health equity. Rural communities suffer significant health disparities relative to urban areas, and also experience internal inequities by race and poverty level. The evaluation framework for The Two Georgias Initiative provides a comprehensive mixed methods approach to evaluating both processes and outcomes. Early results related to community readiness and capacity to address health inequities, measured through a coalition member survey ( n = 236) conducted at the end of the planning phase, suggest coalitions were in the preparation stage, with higher levels of readiness among coalition members and organizations/groups similar to the coalition members' own, lower levels among public officials and other leaders, and the lowest levels among county residents. In addition, coalition members reported more experience with downstream drivers (e.g., access to care) of health than upstream drivers (e.g., affordable housing, environmental or racial justice). By providing a logic model, evaluation questions and associated indicators, as well as a range of data collection methods, this evaluation approach may prove practical to others aiming to evaluate their efforts to address health equity.